If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (q + -7) * 6 = 12 Reorder the terms: (-7 + q) * 6 = 12 Reorder the terms for easier multiplication: 6(-7 + q) = 12 (-7 * 6 + q * 6) = 12 (-42 + 6q) = 12 Solving -42 + 6q = 12 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + 6q = 12 + 42 Combine like terms: -42 + 42 = 0 0 + 6q = 12 + 42 6q = 12 + 42 Combine like terms: 12 + 42 = 54 6q = 54 Divide each side by '6'. q = 9 Simplifying q = 9
| I=15000(0.045)(22/12) | | (e+2)*6=36 | | X+x+2=117 | | (x+4)(2x-3)=6 | | 3x-11=34-2x | | -6x-4=5x-29 | | 5x^2-12x+c=0 | | 2x+24=9x+3 | | 10p+5=80 | | 12X-4=3X^2 | | 7y+2=36 | | P(x)=2x*3-3x*2-120x+100 | | 16y^2-32y-44=0 | | 3x+x=45 | | 10x-11=9x+9 | | 2x+86=6x-6 | | -10=1/2x-9 | | y=1/2*-10-9 | | iz^2+2(1+i)+2=0 | | iz^2+2(1-i)+2=0 | | E=20(11-4) | | (-14/2)x(-21x-3) | | 5n-1-8n=-7-4n | | 3-5b=8-6b | | y=1/2.-10-9 | | x-(4-3x)=6x(x-2) | | -4v+4=-6v | | 12√3/3*√3=? | | 14-1/3x=13 | | 12√3/3*√3= | | 30t+20(t-4)=470 | | -8x+1=1-8x |